Parkinson’s Disease Related Depression and Anxiety: A 22-Year Bibliometric Analysis (2000-2022) - Zhang T; Yang R; Pan J; Huang S (Neuropsychiatric Disease and Treatment, 2023)
Tong Zhang,* Rui Yang,* Juhua Pan, Shijing Huang Research and Development Center of Traditional Chinese Medicine, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shijing Huang; Juhua Pan, Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People’s Republic of China, Email gamhsj@126.com; panjuhua@126.comBackground: Parkinson’s disease (PD) is one of the common neurodegenerative diseases. Depression and anxiety are the most common psychiatric symptoms of PD. It is important to study the potential relationship between PD and depression or anxiety.Aim: This study aimed to use bibliometrics to analyze the papers about parkinson’s disease related depression and anxiety over the last 22 years, and to characterize the current status of research and predict future hotspots.Methods: In the Web of Science Core Collection (WoSCC) from 2000 to 2022, documents are searched according to specific subject words. The selected literature was retrospectively analyzed and mapped using CiteSpace and Vosviewer software. We analyzed countries, institutions, journals, authors, references and keywords.Results: A total of 7368 papers were included from 2000 to 2022, and the number of publications has shown an upward trend year by year. Movement Disorder is the journal with the highest number of publications (391 publications, 5.31%) and citations (30,549 times), with the United States (2055 publications, 27.9%) and the University of Toronto (158 publications) being the countries and institutions with the highest number of publications. The high-frequency keywords focused on “quality of life”, “deep brain stimulation” and “non-motor symptoms”. “Functional connectivity”, “gut microbiota” and “inflammation” may be at the forefront of future research.Conclusion: Parkinson’s disease related depression and anxiety have been increasingly studied over the past 22 years. Functional connectivity, gut microbiota, and inflammation will be the subject of active research hotspots in the future, and these findings may provide new research ideas for researchers.Keywords: Parkinson’s disease, depression, anxiety, bibliometric analysis, Citespace, VOSviewer